1968
DOI: 10.1021/jf60158a015
|View full text |Cite
|
Sign up to set email alerts
|

Para-oxon hydrolyzing enzymes in rat liver

Abstract: H3-Paraoxon was shown to be degraded by at least four distinct enzymes in rat liver with different p H optima, reaction constants, and sensitivities to metallic ions, SH-reagents, and inhibitors. These enzymes were present in a soluble and a particulate state in the liver cell. The specific activity was highest in the crude microsomes and lower in the washed mitochondria and the crude soluble fraction at the respective optimum pH's. The crude soluble fraction contained two different enzymes which were partiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1

Year Published

1975
1975
2001
2001

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(12 citation statements)
references
References 42 publications
3
8
1
Order By: Relevance
“…Our results are similar to those reported for diazoxonase [41] and paraoxonase [42] from rat liver microsomes. However, optimum pH values of 7.7 and 7.4 have been found by others [42,43]. Similar values to those found by us have been reported for paraoxonases from sheep serum [44] and human serum [45].…”
Section: Table 2 Kinetic Constants For Ph and Heat Inactivation Of Rasupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are similar to those reported for diazoxonase [41] and paraoxonase [42] from rat liver microsomes. However, optimum pH values of 7.7 and 7.4 have been found by others [42,43]. Similar values to those found by us have been reported for paraoxonases from sheep serum [44] and human serum [45].…”
Section: Table 2 Kinetic Constants For Ph and Heat Inactivation Of Rasupporting
confidence: 91%
“…The pH optimum determined by us for the purified enzyme (pH 8.5) is identical to that previously reported for rat liver microsomal preparations [40]. Our results are similar to those reported for diazoxonase [41] and paraoxonase [42] from rat liver microsomes. However, optimum pH values of 7.7 and 7.4 have been found by others [42,43].…”
Section: Table 2 Kinetic Constants For Ph and Heat Inactivation Of Rasupporting
confidence: 90%
“…These data suggest some similarity between human plasma and liver paraoxonase. However, the optimum pH found by us for human liver paraoxonase is higher than that reported for other rat liver organophosphorus hydrolases (2,22,23).…”
Section: Effect Of Phcontrasting
confidence: 70%
“…Since divalent metal cations, specifically manganese and/or cobalt in insects or calcium in mammals, act as cofactors for this group of enzymes, this result is not surprising. Kojima and O'Brien [13] similarly reported that EDTA inhibited PTEH activity from rat liver. This result differs, however, from results seen with the tobacco budworm in which the addition of EDTA had no significant effect on PTEH activity [11].…”
Section: Inhibitors and Activation Of Phosphoric Triester Hydrolase Amentioning
confidence: 95%
“…In mammals and insects, the major cation cofactors for phosphoric triester hydrolase are calcium and cobalt/manganese, respectively [10][11][12]. Metal chelators like ethylenediaminetetraacetic acid (EDTA) are inhibitory [13]. Although the exact catalytic mechanism is unknown, it is hypothesized that there is a cysteine group at the active site because mercuric compounds like para-chloromercuribenzoate are potent A-esterase inhibitors [14].…”
Section: Introductionmentioning
confidence: 99%